Ask Advise Connect: A New Approach to Smoking Treatment Delivery in Healthcare Settings - Vidrine, Jennifer Irvin (2013)
BACKGROUND: Several national healthcare-based smoking cessation initiatives have been recommended to facilitate the delivery of evidence-based treatments such as those delivered by quitlines. The most notable examples are the 5 A’s (i.e., Ask, Advise, Assess, Assist, Arrange) and Ask Advise Refer (AAR). Unfortunately, primary care referrals to quitlines are low and the majority of smokers referred fail to call for assistance. This study evaluated a new approach -Ask Advise Connect (AAC) - designed to address barriers to linking smokers with treatment. METHODS: A pair-matched-two-treatment arm group-randomized design in 10 family practice clinics in the Houston, TX metropolitan area was utilized. Five clinics were randomized to AAC (intervention) and five were randomized to AAR (control). In both conditions, clinic staff were trained to assess and record the smoking status of all patients at all visits in the electronic health record (EHR), and smokers were given brief advice to quit. In AAC, the names and phone numbers of smokers who agreed to be connected were sent electronically to the Quitline daily, and patients were proactively called by the Quitline within 48 hours. In AAR, smokers were offered a Quitline referral card and encouraged to call on their own. All data were collected between February and December 2011. The primary outcome – impact – was based on the RE-AIM conceptual framework. Impact was defined as the proportion of all identified smokers that enrolled in treatment. RESULTS: In AAC, 7.8% of all identified smokers enrolled in treatment versus 0.6% in AAR (t(4)=9.19, p=0.0008, OR=11.60 (95% CI 5.53-24.32), a 13-fold increase in the proportion of smokers enrolling in treatment in AAC compared to AAR. CONCLUSIONS: The system changes implemented in AAC could be adopted broadly by other healthcare systems and AAC has tremendous potential to reduce tobacco-related morbidity and mortality.